Entrepreneurship in High School Education - Perspectives of Colombian Teachers - ANGÉLICA RICO; Angela Cardenas (Ignatianum University Press, 2020)
The term entrepreneurship has been seen from a productive perspective, tending towards the development of business ideas. However, today it is also associated with the strengthening of skills and attitudes on a personal level. In Colombia, Law 1014 of 2006 regulates entrepreneurship as part of academic training, at all educational levels. Despite it being an initiative raised by the government, concrete actions on the subject are being directed by teachers in classrooms. For this reason, the views of high school teachers, through the lens of qualitative research, are essential for exploring the reality that education occupies in this aspect, and that increasingly highlights some obstacles which hinder its progress. Therefore, the aim of this article - immersed in the framework of a doctoral thesis about the practices of entrepreneurship among high school teachers in public schools in Bogotá - is to expose which actions have been aimed at integrating entrepreneurship into Colombian high school education from the experience of teachers, as well as to unveil their criticism of the absence of the entrepreneurial process from the first grades established in the law, the role of the National Service of Learning (SENA) as an important institution in Colombia related to entrepreneurship in the classrooms, the lack of a more human vision that is less focused on production in entrepreneurship education, and the huge gap in teacher training in the area.